A mechanistic view on lodging resistance in rye and wheat: a multiscale comparative study. Issue 12 (12th September 2021) - Muszynska, Aleksandra; Guendel, Andre; Melzer, Michael; Tandron Moya, Yudelsy Antonia; Röder, Marion S.; Rolletschek, Hardy; Rutten, Twan; Munz, Eberhard; Melz, Gilbert; Ortleb, Stefan; Borisjuk, Ljudmilla; Börner, Andreas
Summary: The development of crop varieties that are resistant to lodging is a top priority for breeding programmes. Herein, we characterize the rye mutant ´Stabilstroh' ('stable straw') possessing an exceptional combination of high lodging resistance, tall posture and high biomass production. Nuclear magnetic resonance imaging displayed the 3‐dimensional assembly of vascular bundles in stem. A higher number of vascular bundles and a higher degree of their incline were the features of lodging‐resistant versus lodging‐prone lines. Histology and electron microscopy revealed that stems are fortified by a higher proportion of sclerenchyma and thickened cell walls, as well as some epidermal invaginations. Biochemical analysis using Fourier‐transform infrared spectroscopy and inductively coupled plasma‐optical emission spectrometry further identified elevated levels of lignin, xylan, zinc and silicon as features associated with high lodging resistance. Combined effects of above features caused superior culm stability. A simplistic mathematical model showed how mechanical forces distribute within the stem under stress. Main traits of the lodging‐resistant parental line were heritable and could be traced back to the genetic structure of the mutant. Evaluation of lodging‐resistant wheat 'Babax' ('Baviacora') versus contrasting, lodging‐prone, genotype ´Pastor´ agreed with above findings on rye. Our findings on mechanical stability and extraordinary culm properties may be important for breeders for the improvement of lodging resistance of tall posture cereal crops.